The Need for Supervision Model Development to Improve The Competence and Performance of Laboratory Personnel - Wahira Wahira; Ansar Ansar; Abd Hamid (Universitas Negeri Semarang, 2023)
The purpose of this study is to obtain information and an overview of the administrative competence of laboratory personnel and the need to develop a supervision model that will be used by school principals to improve the competence and performance of laboratory staff in Vocational High Schools (SMK). This research uses the Research & Development method with research and development design at the preliminary study stage as needs and content analysis; a data source is a working group of 30 school principals in Sinjai District. The analysis results show that: (1) the competence of laboratory staff in vocational high schools (SMK) based on the analysis of performance appraisal documents in the category is not good. (2) The results of the principal's questionnaire require the development of a supervision model for laboratory personnel. Therefore, this research contributes to and benefits the principal to supervise laboratory staff to improve their competence and performance.